Revising the Assumption that Ḥadīṯ Studies Flourished in the 11th/17th-Century Ḥiǧāz: Ibrāhīm al-Kūrānī’s (d. 1101/1690) Contribution - Dumairieh, Naser (Arabica, 2021)
Abstract The Ḥiǧāz in the 11th/17th century has long been considered the center of a “revival” movement in ḥadīṯ studies. This assumption has spread widely among scholars of the 11th-/17th- and 12th-/18th-century Islamic world based on the fact that the isnād s of many major ḥadīṯ scholars from almost all parts of the Islamic world from the 11th/17th century onward return to a group of scholars in the Ḥiǧāz. The scholarly group that is assumed to have played a critical role in the flourishing of ḥadīṯ studies in the 11th/17th-century Ḥiǧāz is called the al-Ḥaramayn circle or network. However, to date, there have been no studies that investigate what was actually happening in that century concerning ḥadīṯ studies. Examining the actual ḥadīṯ studies of one of the scholars at the core of al-Ḥaramayn circle, i.e . Ibrāhīm b. Ḥasan al-Kūrānī, will unpack the main interest of Ḥiǧāzī scholars in ḥadīṯ literature, reveal previously unstudied aspects of ḥadīṯ studies in the 11th/17th-century Ḥiǧāz, correct some unexamined assumptions, and situate the ḥadīṯ efforts of scholars of the 11th/17th-century Ḥiǧāz within a general framework of developments within ḥadīṯ studies.